Influencia de la proporción de fibra de yute:fibra de vidrio y tratamiento superficial sobre la resistencia a la tracción de un material compuesto de matriz poliéster fabricado mediante el método de compresión - Caballero Garcia, Deives Renee (2018)
In the present investigation, the influence of the proportion of jute fiber: glass fiber and surface treatment on the tensile strength of a polyester matrix composite material, manufactured by the compression method, was evaluated. The proportion of jute fiber: fiberglass used in the evaluation were 1: 1; 2: 1; 3: 1; 4: 1; In addition, natural fibers were worked on long fibers, for synthetic fibers (fiberglass) they were woven bidirectionally; and analyzed the influence they have when the natural fibers are subjected to a surface treatment of mercerization, which was worked at two percentages of NaOH, 5% and 10%. All the specimens were manufactured by the compression method, and formed into 30 cm x 20 cm plates with a thickness of 0.5 cm; subsequently subjected to a cure of 72 hours. The tensile strength was evaluated according to the normal ASTM D-628-01. From the results obtained, it was determined that the tensile strength values obtained are greater in comparison with the composite material, resin and jute fiber; where this compound has an average value of 47.17 MPa; and our test pieces without being subjected to surface treatment, have a minimum tensile strength of 55.47 MPa for the ratio 1: 1; Jute fiber: fiberglass; and maximum of 82.38 MPa for the 3: 1 ratio. Similarly; the tensile strength values obtained are greater in comparison with the composite material, resin and jute fiber; subjected to surface treatment at 5% and 10% NaOH; where this compound presents an average value of 56.27 MPa and 60.60 MPa, respectively; and our test pieces subjected to surface treatment at 5% and 10% NaOH, have a minimum tensile strength of 64.15MPa and 67.49MPa, respectively; for the 1: 1 ratio; Jute fiber: fiberglass; and maximum of 85.55 MPa and 92.22 MPa, respectively; in the ratio of 3: 1. The results are confirmed by analysis of variance for a confidence level of 95% where it concludes that the highest tensile strength is given at 3: 1 proportions, in jute fiber: glass fiber, and with mercerized fibers at 10 % NaOH.